2021
DOI: 10.1111/exd.14450
|View full text |Cite
|
Sign up to set email alerts
|

Skin microbiome alterations in seborrheic dermatitis and dandruff: A systematic review

Abstract: Seborrheic dermatitis (SD) and dandruff (DF) are common chronic inflammatory skin diseases characterized by recurrent greasy scales, sometimes with erythema and itchiness. Although the exact pathophysiology of the disease is still unclear, current theories highlight the role of microbes on the skin surface in the pathogenesis of SD. Here, we conducted a systematic review to investigate the skin microbiome alterations in patients with SD/DF. We searched Medline/PubMed, Embase and Web of Science for research stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
10

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 44 publications
6
41
0
10
Order By: Relevance
“…Our findings of the alteration of the skin fungal community in SD were consistent with those of previous studies. 3,14 A recent systematic review showed that SD was associated with lower fungal diversity compared with healthy individuals, which is consistent with our findings. 3 On investigation of the fungal community and clinical parameters, our study showed a positive correlation between the abundance of Malassezia and disease diversity, indicating that this yeast is an important factor in the pathogenesis of SD.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of the alteration of the skin fungal community in SD were consistent with those of previous studies. 3,14 A recent systematic review showed that SD was associated with lower fungal diversity compared with healthy individuals, which is consistent with our findings. 3 On investigation of the fungal community and clinical parameters, our study showed a positive correlation between the abundance of Malassezia and disease diversity, indicating that this yeast is an important factor in the pathogenesis of SD.…”
Section: Discussionsupporting
confidence: 92%
“…Staphyloccus is linked with epidermal barrier damage, including increased transepidermal water losses and pH, while Cutibacterium increases water content. Malassezia has also been associated with increased pruritus and disease severity ( Xu et al, 2016 ; Park et al, 2017 ; Tao et al, 2021 ).…”
Section: Seborrheic Dermatitismentioning
confidence: 99%
“…Until present, heterogeneity exists between studies assessing the skin microbiome of psoriatic patients, especially the changing trend in the relative abundance of specific bacteria such as Staphylococcus 24–26 . These discrepancies may be due to differences in study population, sampling method, sequencing techniques and analysis method 25,27 . The choice of primers and sequencing targets is the main points of attention in skin microbiome design, and it has strong impact on study results 28 …”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] These discrepancies may be due to differences in study population, sampling method, sequencing techniques and analysis method. 25,27 The choice of primers and sequencing targets is the main points of attention in skin microbiome design, and it has strong impact on study results. 28 In our analysis, the abundance of T. rubrum, which is the most common pathogenic species of onychomycosis, was slightly higher in subjects with NP than psoriatic subjects without nail involvement (7.85% vs. 2.06%, NS).…”
Section: Con Clus I On and Per S Pec Tive Smentioning
confidence: 99%